EFL TEACHERS’ OBSTACLES TOWARDS ICT INTEGRATION IN EFL CLASSROOM CONTEXT - Siti Savira Khaerunnisa; Ilena Faryanis; Amani Rohadatul Aisy; Dila Charisma (University of Kuningan, 2023)
The advancements in ICT have made it possible for knowledge to be shared and acquired quickly. As a result of these developments, it is now imperative that ICT be included into educational settings across the globe. It stresses the need of teachers becoming proficient with ICT in the classroom. Nonetheless, some obstacles impede educators from implementing ICT in the classroom. The present study aims to investigate the obstacles encountered by EFL teachers while attempting to apply ICT in the classroom. This study employs qualitative research by using case study design. This study involved three EFL teachers from three different senior high schools in West Java. The data were collected through semi-structured interview and observation. The findings showed that the absence of ICT integration training, competency, equipment, and proper software and materials are the main challenges faced by English teachers when attempting to integrate ICT.Keywords: obstacles; ICT integration; EFL classroom